WASTE MANAGEMENT POLICY IMPLEMENTATION IN SARI REJO VILLAGE, MEDAN POLONIA SUB-DISTRICT, AND MEDAN CITY - Ikmaluddin Lubis; Sally Marisa Sihombing (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
Medan is one of the cities that has a serious waste problem. As a response to this problem, Regional Regulation Number 6 of 2015 was issued to manage waste in the city of Medan. The purpose of this study is to describe the implementation of waste management policies in Sari Rejo Village, Medan Polonia District, and Medan City. The research method used is descriptive research with a qualitative approach, collecting data, information, or knowledge through in-depth interviews. Determination of informants is done by purposive sampling technique. Data collection techniques included interviews, observations, and documentation related to the implementation of Regional Regulation Number 6 of 2015 in Sari Rejo Village, Medan Polonia District, and Medan City. From the results of the study, it is known that the implementation of Regional Regulation Number 6 of 2015 in Sari Rejo Village, Medan Polonia District, and Medan City is still not optimal. The reason is the absence of a mayoral regulation as a derivative of a regional regulation to serve as an executor in the field. The absence of a mayoral regulation makes the sanctions contained in regional regulations weak. In terms of resources, there are still various obstacles, such as a lack of human resources, equipment resources, and budget resources. Meanwhile, in terms of disposition and bureaucratic structure, it is quite good to promote the implementation of Regional Regulation Number 6 of 2015 in Sari Rejo Village, Medan Polonia District, and Medan City.